POTRET PERKEMBANGAN TEKNOLOGI DALAM DAKWAH ISLAMIAH - Nurfuadi Nurfuadi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2007)
The development of Science was a part of God’s revelation which was revealed to His Prophets at the early awakening of human civilization on the earth. This Science then was spread by their followers to make people understand, apply and develop it as a means in running their duty as caliphs. However, after the death of the prophets, people tended to misuse science development. As a result, beside giving some advantages and ease for human activities, it also creates negative effects.